An introduction to genetic analysis - Suzuki, David T.; Griffiths, Anthony J. F.; Miller, Jeffrey H.; Lewontin, Richard C. (New York Freeman, 1981)
Genetica
Donacion Beatriz Perez
Keywords: Genetica; Mendelismo; Herencia Genetica; Cromosomas; Mapas Geneticos; Mutacion; Numero de Cromosomas; Adn; Genes; Recombinacion; Manipulacion; Genomas; Genetica Cuantitativa; Genetica de Poblaciones